MENGENAL LITERASI ETNOMATEMATIKA DALAM BUDAYA MANGGARAI - Eliterius Sennen (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
In the life of the Manggarai community, numbers 1-10 each have different names or designations. Furthermore, for numbers 10 - 90 there are additional phonemes / m / and followed by the word pulu from numbers 1-9, and specifically for multiples of 10, there is a sound change from / a / to / e /, such as se (ce) mpulu, suampulu , telumpulu, and so on. While numbers 11-19 are a combination of numbers 10 - 90 with numbers 1-9, such as se (ce) mpulu ca, se (ce) mpulu sua, se (ce) mpulu telu, ..., se (ce) mpulu siok (ciok ), suampulu sa / ca, suampulu sua, suampulu telu, ..., suampulu siok / ciok, telumpulu sa (ca), telumpulu sua, telumpulu telu, and so on up to siok (ciok) mpulusiok (ciok). Furthermore, numbers 100 - 900 are called se(ce) ratus, sua ratus, telu ratus, and so on up to Siok (ciok) ratus. Numbers 1000, 2000, 3000, and so on are called ce ribu (ce sebu), sua ribu (sua sebu), telu ribu (telu sebu), and so on. In addition to the base 10 numbers, also found the use of base numbers 2, base 4, base 8, and base 100 as found in the western region of Manggarai. These base numbers 2, base 4, base 8 and base 100 are used in packaging corn. Corn packages consisting of 2 grains are called wasé, packages consisting of 4 grains are called ndurung, packages consisting of 8 grains are called dolé, and packages containing 100 grains or suampulu lima ndurung are called limbung. Various types of tools that are often used by the Manggarai community to say, among others: fingers, corn kernels, dukut ré'a, with measurement units used are: dalo, héndok, pagat, ciku, depa, dako, tongka, wega and so on . The amount of time is: leso, week, lu'ang / wulang, ntaung, and so on. Length measuring instruments commonly used are Ntawang / Ndawang wasé and wasé ajo, the units of which are meters. The length measuring unit commonly used by the Manggarai community is; dalo, héndok, pagat, ciku, depa, and lampa or nggap.